EDUCATIONAL ACTIVITY IN DEVELOPMENT CENTERS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Haqberdiyeva Zamira Rajabboyevna (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article, the importance of development centers in preschool education organizations, the equipment of each group room based on the First Step state program. Information about the dramatized center, the Science and Nature Center.